1958
DOI: 10.1039/jr9580000211
|View full text |Cite
|
Sign up to set email alerts
|

45. The photolysis of pyridoxal phosphate

Abstract: Pyridoxal phosphate, the co-factor of many enzymes involved in aminoacid metabolism, has been found to undergo a rapid, benzoin type, selfcondensation in oxygen-free solution when exposed to light. The main product isolated was shown to be 5 : 5'-bis(dihydroxyphosphiny1oxymethy1) -3 : 3'-dihydroxy-2 : 2'-dimethyl-4 : 4'-pyridil, presumably formed from the corresponding pyridoin during working up in the presence of air.AQUEOUS solutions of pure crystalline pyridoxal phosphate monohydrate (I; X = CHO) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
1

Year Published

1961
1961
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 0 publications
5
40
1
1
Order By: Relevance
“…These results agree well with experiments in which PLP photoproducts isolated after exposure to UV light revealed that the aldehyde group first oxidizes to the acid before dimerizing (Figure 3C). 30,31…”
Section: Resultsmentioning
confidence: 99%
“…These results agree well with experiments in which PLP photoproducts isolated after exposure to UV light revealed that the aldehyde group first oxidizes to the acid before dimerizing (Figure 3C). 30,31…”
Section: Resultsmentioning
confidence: 99%
“…In aerobic conditions, the principal breakdown (oxidation) products include 4-pyridoxic acid-5 0 -phosphate and the dipyridyl a-diketone. In anaerobic conditions, the acyloin is produced (Morrison and Long 1958;Wei et al 1972;Bazhulina et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…PLP was irradiated with light of wavelengths longer than 300 nm in the presence of oxygen [1]. After purification by chromatography on Dowex 1-X-8 resin, two major products were isolated: PPA and bis-PLP (Scheme I).…”
Section: Methodsmentioning
confidence: 99%
“…Bis-PNP was obtained by reduction of bis-PLP with NaBH4 [1]. To a solution of bis-PLP (pH 6), a stoichiometry concentration of NaBH4 was added and allowed to react for 1 h in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation